2023
DOI: 10.3389/fimmu.2023.1074760
|View full text |Cite
|
Sign up to set email alerts
|

The imbalance in the relationship between inflammatory and regulatory cytokines during gestational toxoplasmosis can be harmful to fetuses: A systematic review

Abstract: ObjectiveTo evaluate the available information on inflammatory and regulatory plasma mediators in pregnant women (PW) diagnosed with toxoplasmosis. Source: The PubMed, Embase, Scopus, and Lilacs databases were evaluated until October 2022. Study eligibility criteria: This review was carried out following the PRISMA and registered on the PROSPERO platform (CRD42020203951). Studies that reported inflammatory mediators in PW with toxoplasmosis were considered.Evaluation methodsAfter excluding duplicate articles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…We observed elevated levels of three mediators-neuroserpin, IL-33, and IL-17A-in women with mild DS. Previously, our group demonstrated the involvement of IL-33, CCL2, and IL-17A in pregnant women with T. gondii infection (36)(37)(38). However, neuroserpin was a novel target of this investigation in the context of T. gondii infection and was the only marker elevated in plasma of pregnant women with T. gondii infection having both mild and moderate/severe DS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We observed elevated levels of three mediators-neuroserpin, IL-33, and IL-17A-in women with mild DS. Previously, our group demonstrated the involvement of IL-33, CCL2, and IL-17A in pregnant women with T. gondii infection (36)(37)(38). However, neuroserpin was a novel target of this investigation in the context of T. gondii infection and was the only marker elevated in plasma of pregnant women with T. gondii infection having both mild and moderate/severe DS.…”
Section: Discussionmentioning
confidence: 89%
“…The alarmin IL-33, IL-17A, and the chemokine CCL2 have been highlighted in studies of depressive disorders ( 45 47 ), and their high production/expression was demonstrated in chronic T. gondii research in both experimental models and humans ( 38 , 48 – 50 ). IL-33, which shows high expression in glial cells and astrocytes, has been associated with neurological diseases such as Alzheimer’s, post-traumatic stress disorder, major depressive disorder, and schizophrenia ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…that topical application of IL-6 antibodies significantly improved retinal structure and reduced parasite load, suggesting that IL-6 can induce retinopathy in mice (49). Similarly, T. gondii infection upregulates IL-17 expression, and IL-17 neutralization is partially protective against fatal T. gondii-associated inflammation (43,50). IL-17 is secreted by astrocytes during acute inflammation and is protective against neural cell apoptosis and tissue damage in active uveitis by maintaining homeostasis and inhibiting intracellular calcium increase (51).…”
Section: Intricate Balance Between Inflammatory and Regulatory Cytokinesmentioning
confidence: 93%
“…IL-10 is a potent immunomodulatory cytokine and its deficiency increases the susceptibility to T. gondii infection in mice. IL-10 has been shown to inhibit T. gondii-induced inflammation (43) by suppressing Th1 cell differentiation (44), whereas IL-10 deficiency leads to 4-to 6fold increase in IL-12 and IFN-g (43,45). Thus, IL-10 plays a key role in dampening inflammation and restricting excessive proinflammatory response.…”
Section: Intricate Balance Between Inflammatory and Regulatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation